Service Quality and Customer Satisfaction in Private Sector Banks: An Empirical Study - Vishal Garg (Research Parks Publishers, 2022)
Service Quality in banking sector is the most important criteria and asset for evaluating and satisfying customers and thereby increases the customer loyalty and average retention rate of customers. Among the service quality determinants, reliability, assurance and empathy have always played a pivotal role. During the last two decades, Indian banking industry has undergone remarkable qualitative and quantitative changes and a good number of private commercial banks have gradually captured the market share of banking business not only in metropolitan cities but in small towns as well. In order to capture the market by enhancing the degree of customer satisfaction, private sector banks are expected to provide quality services through dedicated employees and sophisticated technology.